2012
DOI: 10.1103/physrevlett.108.097002
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafast Momentum-Dependent Response of Electrons in AntiferromagneticEuFe2As2Driven by Optical Excitation

Abstract: Employing the momentum sensitivity of time- and angle-resolved photoemission spectroscopy we demonstrate the analysis of ultrafast single- and many-particle dynamics in antiferromagnetic EuFe(2)As(2). Their separation is based on a temperature-dependent difference of photoexcited hole and electron relaxation times probing the single-particle band and the spin density wave gap, respectively. Reformation of the magnetic order occurs at 800 fs, which is 4 times slower compared to electron-phonon equilibration due… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

11
70
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(81 citation statements)
references
References 36 publications
(51 reference statements)
11
70
0
Order By: Relevance
“…The additional component is comparable or faster than the experimental temporal resolution of ∼ 200 fs and compatible with the fastest component measured by TR-ARPES 24 . The slower, previously-observed, shows, differently from TR-ARPES, a divergent-like relaxation time at the respective magneto-structural transition temperatures.…”
Section: -16supporting
confidence: 82%
See 1 more Smart Citation
“…The additional component is comparable or faster than the experimental temporal resolution of ∼ 200 fs and compatible with the fastest component measured by TR-ARPES 24 . The slower, previously-observed, shows, differently from TR-ARPES, a divergent-like relaxation time at the respective magneto-structural transition temperatures.…”
Section: -16supporting
confidence: 82%
“…Previously it was shown, 23,25 that in the SDW state a single ∼ 1 ps relaxation component dominates the nearinfrared narrow-band optical response, while TR-ARPES experiments 24 indicate at least two distinct relaxation processes, with the longest relaxation time similar to the one observed in the optical response.…”
Section: -16mentioning
confidence: 91%
“…For the time scale of the relaxation of near-E F states, we compare the present decay constants with those from previous works. The present value ∼ 0.60 ps for 10 K is close to 0.8 ps for EuFe 2 As 2 [9], 0.38 ps for Ba122 [15] . Also, it is comparable with 0.6-0.8 ps for superconducting Ba 1−x K x Fe 2 As 2 [18] estimated from time-resolved reflectivity.…”
supporting
confidence: 80%
“…Mansart et al [8] reported oscillatory components overlaid on exponential decay in the transient reflectivity spectra of Ba(Fe 0.92 Co 0.08 ) 2 As 2 . TrARPES studies on Ba/EuFe 2 As 2 [9,10] found oscillations of the chemical potential of the electrons after the pump pulse. Time-resolved x-ray diffraction experiments [11,12] measured the oscillations in the intensity of the Bragg reflections from BaFe 2 As 2 (Ba122).…”
mentioning
confidence: 99%
“…Importantly, proper modeling used to analyze experimental findings should account for this behavior, especially when using strong driving fields or studying materials whose physics may manifest the effects of strong correlations. Optical reflectivity, [1][2][3][4][5] photoemission spectroscopy, [1, [6][7][8][9][10][11][12][13][14][15] and resonant x-ray scattering [16][17][18] are equilibrium methods which in the time domain are ideally suited to studying dynamics of novel ordered phases or collective excitations. [2-6, 8-10, 12-18] On sufficiently short time scales, the initial recovery in these systems following an ultrafast pump pulse should be dominated by electron-electron scattering which on its own can drive the system into a new steady-state.…”
mentioning
confidence: 99%